Integration of the Seven Habits of Great Indonesian Children Program into Elementary School Physical Education Learning: A Systematic Literature Review - Rap'i, Rakha Shema Alghahitza Ramiro; Mashud, Mashud (STKIP PGRI Trenggalek, 2026)
The 7 Habits of Indonesian Children (7KAIH) program is a character education initiative designed to develop healthy, well-behaved, and competitive students through the habituation of positive daily behaviors. This study aims to synthesize the implementation of 7KAIH in elementary school Physical Education using a Systematic Literature Review (SLR) approach.This research applies the PRISMA framework and PICO model to determine inclusion and exclusion criteria. Literature was retrieved from Google Scholar covering the period 2016–2026. From an initial 30 identified articles, a systematic screening process including eligibility assessment and quality appraisal was conducted. The synthesis reveals six main themes: physical activity through the Indonesian Children’s Exercise (SAIH), character and religious value strengthening, innovative digital learning media, collaboration between teachers, parents, and schools, inclusive education through adaptive physical activities (Blind SAIH), and health literacy with school policy support. SAIH is identified as the most dominant implementation strategy. Overall, 7KAIH supports holistic physical education by integrating physical, cognitive, affective, social, and inclusive dimensions. This study contributes a synthesized conceptual model that integrates these themes to support instructional strategies, character education, and sustainable policy development in elementary schools.